Eficiencia de uso del nitrógeno en una toposecuencia cultivada con maíz en suelos en pendiente (Agroindustria, Sociedad y Ambiente, 2024)
Corn represents an item of great importance for the Ecuadorian agricultural sector, however, many of the productive areas are located in slope zones, where this factor together with precipitation favors surface runoff, causing considerable losses of nitrogen, being one of the nutrients of greatest demand and that has enormous influence on productivity, so the objective of this research was to evaluate the efficiency of nitrogen use in corn grown commercially through a topsequence of Ecuador. The research was carried out during the rainy season, a completely randomized experiment was conducted with 3 fertilization treatments (absolute control, nitrogen fertilization and complete nitrogen fertilization) and 4 slopes of the field, the following parameters were evaluated: stalk diameter, insertion height, ear length and diameter, 100-seed weight and yield. The results show that fertilization increased nitrogen use efficiency, development and yield. However, it should be noted that the efficiency of nitrogen uses in relation to N applied fell from 0.76 to 0.46 kg N absorbed/kg N and 58.5 to 41.7 kg grain/kg N respectively as the slope increased, which shows that crop fertilization must be accompanied by conservation practices that reduce losses due to runoff and erosion, particularly in soils with high slopes and intense precipitation as those evaluated.
Keywords: conservation, runoff, erosion, slope, sustainability